Mathematics Learning Innovation for Student Mathematics Process Skills in Higher Grade of Elementary Schools - Kamid; Ramalisa, Yelli; Fajriah, Noor; Kurniawan, Dwi Agus; Perdana, Rahmat; Putri, Fhadira Insani; Prameswari, Nirmala; Fadillah, Agus (Universitas Pendidikan Ganesha, 2024)
The process skills approach can improve students' mathematical connection abilities, because it requires students to be active and creative in knowing the relationship between mathematical concepts and everyday life. If students do not have process skills in learning mathematics, they will have difficulty understanding and working on mathematical problems. The purpose of this research is to analyze processing skills differ in grade 4 mathematics learning on multiples and number factors in elementary school. The research method used is a mixed method. This research was conducted in class 4 of elementary school. The sample used in this research was 18 students selected using purposive sampling technique. The instruments used were observation, interviews and questionnaires. Data analysis techniques use descriptive and inferential statistics. Descriptive statistics to determine minimum values, maximum values, mean, median, and mode as well as inferential statistics to test assumptions and test hypotheses. Meanwhile, the process skills carried out in this research can improve students' mathematical connection abilities because students are required to be active and creative so they can understand the relationship between concepts in mathematics and their application in everyday life.